Socialization of Drawing Technique with Inventor Software for High School Student - Ilham Arifin Pahlawan; Alviani Hesthi Permata Ningtyas; Irfan Arif Evendi (Universitas Muhammadiyah Gresik, 2022)
In today's digitalization era, the sensitivity of using design and illustration software is a demand in improving the competencies possessed by students at the high school level. This ability will support students' interests and talents by adjusting the Project Based Learning Program owned by SMAM 1 Gresik, namely the L800 Motorcycle Modification Automotive Project. By introducing and training students using the design and illustration software used, namely Autodesk Inventor: Student Version, This training activity aims to (1) Students are able to use the Autodesk Inventor Application in 2D and 3D schemes, (2) Students are able to gain an understanding of motor engineering components and motor engineering drawings, (3) help teach teachers who teach subjects in the field of applied science. The methods used in this community service are teaching, demonstration and practice methods. The result of this community service is to improve the ability of the participants in terms of designing and modifying the practice of observing L800 motorcycle components and students more easily understand the shape of an Engineering component through Technical Drawings effectively and efficiently due to virtual 3D modeling in the Autodesk Inventor application.